Influence of emicizumab on protein C-mediated clotting regulation - Federica Mancazzo; Antonia Vitulli; Lavinia Dirienzo; Concetta T. Ammollo; Fabrizio Semeraro; Mario Colucci (Bleeding, Thrombosis and Vascular Biology, 2023)
Emicizumab, a FVIII-mimetic bispecific antibody, is insensitive to degradation by activated protein C (APC) and may thus induce a procoagulant state. We investigated the effect of emicizumab on protein C-mediated inhibition of coagulation under in vitro conditions mimicking physiological and pathological clotting activation. Thrombin generation (TG) in tissue factor-triggered hemophilic plasma containing emicizumab (50 μg/mL) was inhibited by APC or thrombomodulin in a concentration-dependent manner, and to a similar extent as in plasma added with FVIII (Kovaltry, 1 IU/mL). However, when clotting was activated via the intrinsic pathway, emicizumab-plasma displayed resistance to APC, manifested by a barely detectable prolongation of the lag time of TG, and by the lack of inhibition of FXa generation. Moreover, in contact-activated plasma added with APC, the generation of a second wave of thrombin, following prothrombin replenishment, was much greater in emicizumab-plasma than in Kovaltry-plasma, suggesting that the insensitivity of emicizumab to APC may translate in greater thrombin formation. Considering the major role played by the contact system in the thrombotic process, hemophilia A patients under emicizumab treatment might be at increased thrombotic risk.